Peningkatan Literasi Multikultural Guru Pondok Pesantren Darussalam Gontor Kampus Putri Melalui Experiential Learning - Yahya, Yuangga Kurnia; Majid, M. Kharis; Setiawan, Muhammad Nurrosyid Huda; Karomi, Kholid; Junana, Olivia Fiestha; Az Zuhroh, Talia; Nugraheni, Arfita Maula; Nasywadina, Nyiar; Kurnia, Farhana Ovista (Universitas Muhammadiyah Mataram, 2026)
Abstract: The diverse activities and social backgrounds within Islamic boarding schools constitute valuable social capital for strengthening social cohesion in society. However, limited direct encounters with communities of different religious and ethnic backgrounds outside the pesantren environment may constrain the development of multicultural literacy. This community service program aims to enhance the multicultural literacy of teachers at Darussalam Gontor Islamic Boarding School for Female Students through an experiential learning approach based on direct engagement with multicultural communities. The implementation method consisted of three stages: preparation, implementation, and evaluation, carried out through enrichment lectures, discussions, field visits, reflective sessions, and direct interactions with interfaith and interethnic communities in Malaysia. The results indicate an improvement in participants’ cultural awareness, experiential understanding, and intercultural sensitivity, particularly in relation to diversity management and the development of inclusive and dialogical social attitudes. These direct experiences strengthened the participants’ readiness to engage constructively in multicultural societies and to contribute to the reinforcement of social cohesion in their respective fields of service.Abstrak: Kehidupan pesantren yang diwarnai oleh keragaman latar belakang santri dan guru merupakan modal sosial penting dalam penguatan kohesi sosial di masyarakat. Namun, keterbatasan perjumpaan langsung dengan masyarakat lintas agama dan etnis di luar lingkungan pesantren berpotensi membatasi pengembangan literasi multikultural. Kegiatan pengabdian ini bertujuan untuk meningkatkan literasi multikultural guru Pondok Pesantren Darussalam Gontor Kampus Putri melalui pendekatan experiential learning berbasis perjumpaan langsung dengan masyarakat multikultural. Metode pelaksanaan kegiatan meliputi tahap persiapan, pelaksanaan, dan evaluasi yang diwujudkan dalam bentuk kuliah pengayaan, diskusi, kunjungan lapangan, refleksi, serta interaksi langsung dengan komunitas lintas agama dan etnis di Malaysia. Hasil kegiatan menunjukkan adanya peningkatan wawasan, pengalaman, dan sensitivitas budaya peserta terhadap realitas multikultural, khususnya dalam memahami pengelolaan keragaman agama dan etnis serta membangun sikap inklusif dan dialogis dalam interaksi sosial. Pengalaman langsung ini memperkuat kesiapan peserta untuk berperan aktif dalam masyarakat multikultural serta berkontribusi pada penguatan kohesi sosial di lingkungan tempat mereka mengabdi.